A simple, high-throughput stabilization assay to test HIV-1 uncoating inhibitors - Dostálková, Alžběta; Hadravová, Romana; Kaufman, Filip; Křížová, Ivana; Škach, Kryštof; Flegel, Martin; Hrabal, Richard; Ruml, Tomáš; Rumlová, Michaela (Scientific reports, 2019)
Shortly after entering the cell, HIV-1 copies its genomic RNA into double-stranded DNA in a process known as reverse transcription. This process starts inside a core consisting of an enclosed lattice of capsid proteins that protect the viral RNA from cytosolic sensors and degradation pathways. To accomplish reverse transcription and integrate cDNA into the host cell genome, the capsid shell needs to be disassembled, or uncoated. Premature or delayed uncoating attenuates reverse transcription and blocks HIV-1 infectivity. Small molecules that bind to the capsid lattice of the HIV-1 core and either destabilize or stabilize its structure could thus function as effective HIV-1 inhibitors. To screen for such compounds, we modified our recently developed FAITH assay to allow direct assessment of the stability of in vitro preassembled HIV-1 capsid-nucleocapsid (CANC) tubular particles. This new assay is a high-throughput fluorescence method based on measuring the amount of nucleic acid released from CANC complexes under disassembly conditions. The amount of disassembled CANC particles and released nucleic acid is proportional to the fluorescence signal, from which the relative percentage of CANC stability can be calculated. We consider our assay a potentially powerful tool for in vitro screening for compounds that alter HIV disassembly.
Keywords: Viral Core Proteins; Base Sequence; proteiny virového jádra; rychlé screeningové testy; sekvence aminokyselin; HIV Infections; Nucleocapsid; Anti-HIV Agents; RNA, Viral; HIV-1; lidé; High-Throughput Screening Assays; svlékání virového obalu; Amino Acid Sequence; HIV infekce; RNA virová; nukleokapsida; sekvence nukleotidů; Virus Uncoating; látky proti HIV; Humans